Controlling Hypertension After Severe Cerebrovascular Event (CHASE): A randomized, multicenter, controlled study. Issue 4 (June 2021) - Yuan, Fang; Yang, Fang; Zhao, Jingjing; Fu, Feng; Liu, Yi; Xue, Changhu; Wang, Kangjun; Yuan, Xiangjun; Li, Dingan; Liu, Qiuwu; Zhang, Wei; Jia, Yi; et al.
Background: The optimal blood pressure lowering target in the acute phase of severe stroke is uncertain. Our aim was to compare the efficacy and safety of individualized blood pressure lowering with standard blood pressure lowering in severe stroke. Methods: Five-hundred consecutive patients with acute severe stroke and elevated BP were recruited from 26 Chinese hospitals. Eligible patients were randomized into an individualized blood pressure lowering group (with 10–15% reduction in systolic blood pressure from admission level or standard blood pressure lowering group (with a target SBP of <200 mm Hg in acute ischemic stroke and <180 mm Hg in intracerebral hemorrhage). The primary outcome was the proportion of patients with a poor functional outcome at day 90 of enrolment. Results: Of 483 participants included in the analysis, 242 received individualized blood pressure lowering treatment and 241 received standard treatment. The primary outcome event was observed in 71.1% of the participants in the individualized treatment group and in 73.4% of the standard treatment group (odds ratio with individualized treatment for primary outcome, 0.75; 95% confidence interval, 0.47 to 1.19; p  = 0.222). The rates of serious adverse events in the two groups were similar (27.7% vs. 28.2%). Conclusions: In patients with acute severe stoke, individualized blood pressure lowering treatment did not significantly reduce the rate of three-month death or dependence. Trial registration: Clinicaltrials.gov, NCT02982655. Registered in 5 December 2016, https://clinicaltrials.gov/ct2/show/NCT02982655